1981
DOI: 10.3382/ps.0600623
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an Indigestible Material on Energy Excretion by Roosters and on True Metabolizable Energy of Corn

Abstract: The influence of an indigestible and noncombustible material, silica gel (SG) on the excretion of energy by roosters and on the true metabolizable energy (TME) of corn was determined. Energy excretion by fasted roosters increased linearly with each increment of SG force-fed. The equation, energy excreted (kcal/24 hr) = 9.87 + (.47 x g SG) described this effect of SG. The data also showed that 24 hr was insufficient time for SG to completely clear the digestive tract, irrespective of amount force-fed. The TME o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…The main reason for this difference is likely the variation in the chemical composition of these feedstuffs, especially in neutral detergent fiber. ME has been shown to be strongly correlated with the content of indigestible materials, such as fiber (Tenesaca and Sell, 1978;Farrell, 1981). The present study supports the conclusion that excreted energy output can be increased with an increase in the neutral detergent fiber content in the feed, thereby reducing the finial ME estimates.…”
Section: Discussionsupporting
confidence: 87%
“…The main reason for this difference is likely the variation in the chemical composition of these feedstuffs, especially in neutral detergent fiber. ME has been shown to be strongly correlated with the content of indigestible materials, such as fiber (Tenesaca and Sell, 1978;Farrell, 1981). The present study supports the conclusion that excreted energy output can be increased with an increase in the neutral detergent fiber content in the feed, thereby reducing the finial ME estimates.…”
Section: Discussionsupporting
confidence: 87%
“…Muztar and Slinger (1980c) also found that supplementary cellulose had no effect on amino acid excretion. Tenesaca and Sell (1981) found the TME value of corn to decrease as dilution with silica gel increased and attributed the effect to the silica increasing F,,E+U.E. Individually sand and grir (25 g/kg) did not affect the TME value of a diet but in combination they increased TME whereas a cellulose supplement decreased the dietary TME value (Miles et al 1981).…”
Section: Assay Environmentmentioning
confidence: 99%
“…Sibbald (1960) encontrou valores mais precisos quando utilizou óxido crômico como indicador fecal, enquanto Potter (1972) concluiu que os melhores resultados foram obtidos pelo método de coleta total de excretas. De acordo com Tenesaca & Sell (1981), 24 horas de coleta foram insuficientes para esvaziar o TGI quando se utilizou sílica diluída em uma ração basal. Semelhantes resultados foram encontrados por Parsons et al (1982), que propuseram o período de 30 horas de coleta como o mais preciso.…”
Section: Introductionunclassified